Cultivating OBE Competencies in Emerging Engineering Disciplines to Serve New Quality Productive Forces - Zhao, Yanling; Wu, Xiaoming; Ma, Bin; Liu, Guangqi (Journal of Educational Research and Policies, 2025)
The connotation and evolution of new quality productive forces represent a core driver for high-quality economic development, placing new demands on competency cultivation in emerging engineering disciplines. This paper first interprets the essence of developing new quality productive forces and analyzes the corresponding higher requirements for talent cultivation in emerging engineering fields. Subsequently, it examines the advantages of the Outcome-Based Education (OBE) philosophy and elaborates on how integrating emerging engineering discipline construction with OBE competency cultivation serves as a crucial pathway for enhancing the level of new quality productive forces. Finally, using the development of an emerging engineering discipline (Computer Science) at a provincial university as a case study, it outlines methods and strategies for cultivating professional talents’ OBE competencies from the perspective of developing new quality productive forces, aiming to provide robust talent support for industrial upgrading and socio-economic development.